Evaluasi Kepuasan Pelanggan Di Poltekkes Kemenkes Palangka Raya Tahun 2017 - Gad Datak; Lamia Diang Mahalia; Riyanti Riyanti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
The quality of education service can observe with how the institution gives a quality asurance. The government pass-through Kepmenpan No: KEP/25/M.PAN/2/2004 have made guedeline to assess of costumers satisfaction for every institution belonging to the educational institution. Health Polytechnic Palangka Raya as an educational institution has given education serve need to measure costumers satisfaction. The survey has been a method on this research with a questioner as the instrument. 437 people have been a respondent on this research consists of student, lecturer, staff, parent, alumni, and stakeholder. The result of the research have shown the student, lecturer, and parent satisfaction index value belonging to a good actual performance and very good for staff, alumni, and stakeholder. Thereby, it is generally that educational services on Health Polytechnic Palangka Raya were given satisfaction to the student, lecturer, staff, parent, alumni, and stakeholder.